Health education module based on information–motivation–behavioural skills (imb) for reducing depression, anxiety, and stress among adolescents in boarding schools: a clustered randomised controlled trial - Rahmat Dapari; Mohd Safrin Mohamad Bashaabidin; Mohd Rohaizat Hassan; Nazri Che Dom; Syed Sharizman Syed Abdul Rahim; Wan Rozita Wan Mahiyuddin (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Depression, anxiety, and stress (DAS) among adolescents have become a public health concern. The aim of this study was to develop, implement, and measure an IMB-based health education intervention module for reducing DAS among adolescents in boarding schools in the state of Negeri Sembilan, Malaysia. A single-blinded cluster randomised control trial (RCT) was conducted among students with abnormal DASS-21 scores. They were divided into an intervention group (three schools, 62 participants) and a control group (three schools, 57 participants). Participants in the intervention group received IMB-based health education, while participants in the control group underwent the standard care session. To determine the effectiveness of the intervention, the Generalised Linear Mixed Model (GLMM) analysis was conducted. A total of 119 students participated in this study, and no loss to follow-up was reported. Both intervention and control groups showed significantly reduced DAS scores (p < 0.005). However, the reduction of these scores was greater in the intervention group. The GLMM analysis revealed that the intervention was effective in reducing depression (ß = −2.400, t = −3.102, SE = 0.7735, p = 0.002, 95% CI = −3.921, −0.878), anxiety (ß = −2.129, t = −2.824, SE = 0.7541, p = 0.005, 95% CI = −3.612, −0.646), and stress (ß = −1.335, t = −2.457, SE = 0.536, p = 0.015, 95% CI = −2.045, −0.266) among adolescents. The IMB-based health education module was effective in reducing DAS among adolescents in boarding schools.